2017
DOI: 10.3382/ps/pew195
|View full text |Cite
|
Sign up to set email alerts
|

Apparent metabolizable and net energy values of corn and soybean meal for broiler breeding cocks

Abstract: The AME and net energy (NE) values of 4 corn varieties, including 2 normal corn varieties (Zheng Dan 958 and Xian Yu 335), and one each of waxy corn and sweet corn, and 2 soybean meal samples including regular (RSBM) and dehulled soybean meal (DSBM), were determined in 2 experiments for broiler breeding cocks using the indirect calorimetry method. The 4 test diets in Experiment 1 consisted of each test corn, which replaced 40% of the corn-soybean meal basal diet, and the test diets in Experiment 2 contained 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 40 publications
7
28
4
Order By: Relevance
“…(2019b) in laying hens, respectively, in the corns. The AME values of 3,785 and 3,775 kcal/kg DM for 2 corn samples determined by the substitution method in broiler breeding cocks in our previous study ( Liu et al., 2017 ) were higher than the values for corn 1 and 2 in the present study.…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…(2019b) in laying hens, respectively, in the corns. The AME values of 3,785 and 3,775 kcal/kg DM for 2 corn samples determined by the substitution method in broiler breeding cocks in our previous study ( Liu et al., 2017 ) were higher than the values for corn 1 and 2 in the present study.…”
Section: Resultscontrasting
confidence: 91%
“…The calculated NE values (2,682 and 2,829 kcal/kg DM) are close to the measured NE values (2,575 and 2,693 kcal/kg DM) for corn 1 and corn 2, respectively. The NE values of the 2 corn samples in the present study are lower than 2,982 and 3,006 kcal/kg DM previously reported by Liu et al. (2017) for 2 corn samples determined using the substitution method in broiler breeding cocks.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…Titanium dioxide (TiO 2 ) was added to diets at 0.4%, as an exogenous digestibility marker. The proportional replacement of the energy-yielding components was essential for the calculation of AME for FRSM and RSM [ 18 , 19 ]. Table 2 shows the ingredients and chemical compositions of the reference and experimental diets.…”
Section: Methodsmentioning
confidence: 99%
“…In livestock production, energy is one of the limiting factors in animal performance [44]. ME is the commonly used trait for evaluating energy content of feed [45]. Napier grass genotypes were within the range of ME content for tropical grasses [44].…”
Section: Genotypic Performance For Feed Nutritional Qualitymentioning
confidence: 99%